The Logic of Feeling - Tuan Pham, Michel (Journal of Consumer Psychology, 2004)
The contribution of the feelings‐as‐information hypothesis to our understanding of the role of affect in judgment and decision making is discussed. Basic principles and regularities in how affective feelings guide judgments and decisions are then identified. Based on these principles and regularities, it is argued that the role of feelings in judgment and decision making may be more adaptive than has been assumed in most academic circles. This adaptivity transpires (a) in the variety of goal‐relevant signals that feelings convey, (b) the flexibility with which feelings are interpreted, (c) the judgmental properties of feelings, and (d) the selectivity with which feelings are invoked. It is speculated that affective feelings may tap into a separate system of judgment and decision making with its unique strengths and weaknesses.